The Problems of Ideas in the Muslim World - Mohamed Wagialla Ahmed (International Institute of Islamic Thought, 1998)
This is a good English translation of a slim volume originally published in French under the title, Le Probleme des Ideas dans le Monde Musulman. The book is composed of 17 essays, the culmination of the intellectual life of its author, the late Malik Bennabi. The book insightfully deals with a problem heretofore neglected by most authorities on Islamic thought: the problem of ideas in the Muslim world. The central theme of the book builds on the close linkage between ideas and their cultural environment, which determines whether ideas are dead, deadly, or efficient. As an original thinker, Bennabi identifies the problem of the Muslim world as civilizational and cultural in nature. Bennabi's contribution to modem Muslim thought lies, in principle, in his attempt to discover the universal laws that govern the perfonnance of human civilization from birth, growth, prosperity, expansion, decline, and disintegration and to apply these laws to the history of ideas in the Muslim world. He postulates that the social process takes its course in the history of civilizations and cultures, revealing itself in the dynamics of three major realms: persons, objects, and ideas, the latter being the focus of his book. Bennabi perceives the post-Muwahid or postcivilized Muslim world as lacking the spirit of creativity and falling into a process of ad hoc borrowing of ready-made objects and ideas from the West without due concern for the preconditions of their viability and applicability. In order to analyze this situation, the author develops a framework of analysis by which regional issues and minute details find their place and acquire their significance within a comprehensive and integrated whole, which in itself poses a real challenge to the paradigm currently dominating the realm of ideas in the Muslim world ...